2022
DOI: 10.3390/cancers14225546
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Penetrating Peptides (CPPs) as Therapeutic and Diagnostic Agents for Cancer

Abstract: Cell-Penetrating Peptides (CPPs) are short peptides consisting of <30 amino acids. Their ability to translocate through the cell membrane while carrying large cargo biomolecules has been the topic of pre-clinical and clinical trials. The ability to deliver cargo complexes through membranes yields potential for therapeutics and diagnostics for diseases such as cancer. Upon cellular entry, some CPPs have the ability to target specific organelles. CPP-based intracellular targeting strategies hold tremendous po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 165 publications
0
19
0
Order By: Relevance
“…Especially in cancer, many examples of CPPs employed as therapeutic tools are present and some of them are involved in pre-clinical and clinical trials. [170,201,202] Despite the large amount of research and pre-and clinical studies carried out till now (Table 7), no CPPs or CPP/cargo formulations have been approved by EMA or FDA and several clinical trials have been unsuccessfully terminated. In fact, many issues may hamper translation of CPPs into clinics, even if many of them may be overcome in different ways.…”
Section: Clinical and Diagnostic Applications Involving Cppsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially in cancer, many examples of CPPs employed as therapeutic tools are present and some of them are involved in pre-clinical and clinical trials. [170,201,202] Despite the large amount of research and pre-and clinical studies carried out till now (Table 7), no CPPs or CPP/cargo formulations have been approved by EMA or FDA and several clinical trials have been unsuccessfully terminated. In fact, many issues may hamper translation of CPPs into clinics, even if many of them may be overcome in different ways.…”
Section: Clinical and Diagnostic Applications Involving Cppsmentioning
confidence: 99%
“…From their first discovery in late 80 s, [14,200] CPPs have evolved in their applications as potential clinical and diagnostics tools, till reaching clinical trials for different pathologies. Especially in cancer, many examples of CPPs employed as therapeutic tools are present and some of them are involved in pre‐clinical and clinical trials [170,201,202] . Despite the large amount of research and pre‐ and clinical studies carried out till now (Table 7), no CPPs or CPP/cargo formulations have been approved by EMA or FDA and several clinical trials have been unsuccessfully terminated.…”
Section: Clinical and Diagnostic Applications Involving Cppsmentioning
confidence: 99%
“…From this aspect, F I G U R E 8 Targeting organelle using cell-penetrating peptide (CPPs). The figure was reprinted from (Bottens & Yamada, 2022) with the permission of MDPI.…”
Section: Recent Advances In Predictingmentioning
confidence: 99%
“…The next stage of CPP‐based development of targeting cancer cells is linked with intracellular targeting using some amino acid sequences that support the localization of drug means in organelles. A recent review by Bottens and Yamada highlights intracellular targeted delivery of anticancer agents using CPP (Bottens & Yamada, 2022). This approach requires designing and checking of already known sequences specific for organelles: mitochondria, endoplasmatic reticulum, nucleus, etc.…”
Section: Intracellular Targeting By Cppsmentioning
confidence: 99%
“…A slower elimination rate can be specifically helpful when using peptides for enhancing drug transport to increase their time inside the organism. Some studies have suggested that some CPPs have enhanced uptake efficacy and delivery efficiency than other similar treatments, such as nanoparticles, while presenting less cytotoxicity [26]. Indeed, several peptides have already entered Phase I, Phase II and even, Phase III clinical trials [2].…”
Section: In Silico Evaluation Of the Pk Properties Of Peptides P1-p4mentioning
confidence: 99%